2004
DOI: 10.1007/s10549-004-1282-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of single agent capecitabine in pretreated metastatic breast cancer patients from the French compassionate use program

Abstract: Capecitabine is active in heavily pretreated MBC patients and has a favorable toxicity profile with the added advantage of being an oral drug administered in an outpatient setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 22 publications
3
12
1
Order By: Relevance
“…This safety profile is consistent with that observed in previous studies of capecitabine monotherapy [3,4,5,7,8,9,10,11, 14] or in other named-patient or compassionate-use programs in patients with MBC [16, 17]. In phase II and III trials, the most frequently reported clinical adverse events were hand-foot syndrome (18–71%), diarrhea (28–58%) and nausea (34–55%) [3,4,5, 7, 9].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This safety profile is consistent with that observed in previous studies of capecitabine monotherapy [3,4,5,7,8,9,10,11, 14] or in other named-patient or compassionate-use programs in patients with MBC [16, 17]. In phase II and III trials, the most frequently reported clinical adverse events were hand-foot syndrome (18–71%), diarrhea (28–58%) and nausea (34–55%) [3,4,5, 7, 9].…”
Section: Discussionsupporting
confidence: 91%
“…In phase II and III trials, the most frequently reported clinical adverse events were hand-foot syndrome (18–71%), diarrhea (28–58%) and nausea (34–55%) [3,4,5, 7, 9]. As in the present study, slightly lower incidences of these events were reported in named-patient or compassionate-use studies (36 and 54, 33 and 36 and 24 and 31%, respectively) [16, 17]. It is plausible that in the latter studies, minor toxicities were less likely to be documented than in trials with rigorous formal protocols.…”
Section: Discussionsupporting
confidence: 64%
“…In a recent retrospective analysis of 197 patients previously treated with an anthracycline, taxane, and/or vinorelbine (French compassionate-use program) [27], multivariate analyses showed that a favorable response to capecitabine therapy was associated with longer survival (relative risk [RR], 5.2; 95% CI, 2.0-13.6; p = .001). Another retrospective study that included 113 anthracycline-and taxane-refractory patients [52] reported that those treated with single-agent capecitabine had a significantly longer MOS time than those treated with single-agent vinorelbine (6.2 vs. 3.4 months; p < .0001).…”
Section: Efficacymentioning
confidence: 99%
“…Its efficacy has been proven through many clinical trials [10,11,12,13,14]. Both capecitabine and S-1 are classified as 5-FU anti-neoplastic agents, but it is known that their profiles of adverse effects are different.…”
Section: Discussionmentioning
confidence: 99%